The Effect Of Training, Wage Patterns, Occupational Health And Safety On Work Motivation Of Small And Medium Footwear Industry Clushter In Mojokerto City - Sonang Sitohang; Sasi Agustin; Firdaus Marsahala (Institute of Computer Science (IOCS), 2021)
occupational health and safety on work motivation of small and medium-sized footwear industrial Clushter in Mojokerto. The research model with developing hypotheses is derived based on the literature. To provide empirical evidence, this study conducted a survey and data collection using a questionnaire list, and saturated sampling of 35 employees of small and medium-sized footwear industrial Clushter in the city of Mojokerto. The results showed that training had a negative and significant effect on Employee Motivation at Small and Medium Footwear Industry Clushter in Mojokerto City. This indicates that the implementation of the training is not in accordance with the needs of the training participants. This condition shows that employee work motivation has actually decreased after the implementation of the training. The implementation of training should be an effort to provide information for employees, skills and an explanation of the goals to be achieved by the company so that employees will be motivated to work more efficiently and effectively. Wage patterns have a positive and significant effect on the Work Motivation of the Employees of the SMEs Footwear Clushter in Mojokerto. Occupational Health and Safety has a negative and significant effect on Employee Work Motivation at Small and Medium Footwear Industry Clushter in Mojokerto City The availability of work facilities both in quantity and quality without optimal utilization and a high understanding of work procedures will not increase employee motivation, instead it will reduce work motivationtions.